Student Interactions with AI Chatbots in Academic Activities: A Qualitative Study at Universitas Islam Bunga Bangsa Cirebon - Fauzi, Rifqi; Amaliyyah, Nida; Ningsih, Widia (International Journal of Social Service and Research, 2025)
The rapid advancement of artificial intelligence, particularly AI chatbots such as ChatGPT, has fundamentally transformed the ways in which students engage with academic activities in Islamic higher education institutions. This study aims to analyze the patterns of interaction and communication experiences of students at Universitas Islam Bunga Bangsa Cirebon (UI BBC) in utilizing AI chatbots for academic purposes, examined through the theoretical lens of Computer-Mediated Communication (CMC). Employing a descriptive qualitative approach, the research conducted in-depth interviews with ten purposively selected students. The findings identify four principal interaction modalities: transactional-rapid, elaborative-dialogic, productive-generative, and reflective-critical. A distinctive finding reveals that Islamic values such as amanah (trustworthiness) and thalabul ilmi (the pursuit of knowledge) function as ethical moderators in students’ utilization of AI. This study recommends the development of an AI literacy program grounded in Islamic values. In conclusion, AI chatbots have become important communication partners in students’ academic activities, offering both opportunities and challenges for higher education. The study implies the importance of developing value-based AI literacy programs, strengthening ethical awareness, and designing pedagogical strategies that integrate AI technology productively while maintaining academic integrity and Islamic educational values.